EFFECTIVENESS INSTRUMENT TEST ON PLAY-BASED METHOD OF FOOTBALL‘S WARM-UP MODEL - Qorry Armen Gemael; Deden Akbar Izzuddin; Rolly Afrinaldi (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
This study aims to determine the value of the validity and reliability of the effectiveness instruments of football warm-ups with a play-based method involving students of the University of Singapore in Karawang who took a football course as a research sample consisting of 20 students. The research method used is descriptive research and data collection techniques using test and measurement methods. The instrument used in this research and development was a warm-up instrument used to collect subject data, the results of the sit and reach instrument validity test was 0.979, the Static Flexibility Test - Ankle was 0.913, the Standing balance test was 0.942 while the results of the sit and reach reliability test , Static Flexibility Test - Ankle, and Standing balance of 0.940. From the results of the validity and reliability test, the instrument warm-up can be used. Researchers suggest that warm-up instruments be used by coaches to measure muscle, joint and body balance in soccer athletes, especially in the Karawang area of ​​West Java.